Relativism and marketing: A methodological proposal for the consumer behavior study (2011)
During decades the positivism has dominated the academic and researching environment.This article wants to express, by sharing elements of a specific researching experience(about consumer behaviour, in this case), that relativism as philosophy for approaching tosocial phenomena is appropriated and also rigorous. An anthropological and sociologicaldoctrine, which gives theoretical and methodological support to research duties, are tackled.Ethnography, the classic method of anthropological research and its main techniques fordata collecting are explained. The process for data treatment, under PRODIN methodologyof qualitative analysis is also shown.